Monaco and film dosimetry of 3D CRT, IMRT and VMAT cases in a realistic pelvic prosthetic phantom. (April 2018) - Ade, Nicholas; du Plessis, F.C.P.
Abstract: The dosimetry of patients with metallic hip implants during irradiation of pelvic lesions is challenging due to dose distortions caused by implants. This work presents a dosimetric comparison of various multi-field photon-beam dose distributions in the presence of unilateral hip titanium prosthesis (UHTiP) embedded in a unique pelvic phantom made out of water-equivalent nylon slices. The impact of the UHTiP on the accuracy of dose calculations from a Monaco TPS (treatment planning system) using the X-ray voxel Monte Carlo (XVMC) algorithm was benchmarked against measured dose data using Gafchromic EBT3 film. Multi-field beam arrangements including a 4-field box, 5-field 3DCRT (three-dimensional conformal radiation therapy), 6-field IMRT (intensity modulated radiation therapy) and a single-arc VMAT (volumetric modulated arc therapy) plan were set up for 6 MV and 15 MV beams. These plans were generated for the pelvic phantom that contains the prosthesis with film inserted. Compared to Monaco TPS dose calculations, film measurements showed enhanced dose in the prosthesis which was not predicted by Monaco due to its limitation in relative density assignment. The enhanced prosthesis dose increased with increase in beam energy and decreased with the complexity of the treatment plans, with VMAT giving the least escalated dose. The dose increased between 5% and 19% for 6 MV and between 6% and 21% for 15 MV. A gamma index analysis showed that 70–92% of dose points (excluding the prosthesis) were within 3% discrepancy. Increasing the number of treatment fields increases target dose coverage and improves the agreement between film and Monaco. When the relative electron density (RED) in the prosthesis was varied between 3.72 and 15 the dose discrepancy between film and Monaco increased from 30% to 57% for 6 MV and from 30% to 50% for 15 MV. The study indicates that beam weights for fields that pass through the prosthesis should be minimised and its RED must be correct for accurate dose calculation on Monaco. Highlights: A realistic pelvic phantom with embedded hip Ti prosthesis is studied. Film and Monaco dose data for various 6 and 15 MV treatment plans were evaluated. Compared to Monaco, film measurements showed enhanced dose in the prosthesis. Outside the prosthesis, film and Monaco dose data agreed within 3%. Increasing number of treatment fields resulted to less perturbed dose.